Improve of the call center service from knowledge management - Valencia Rodríguez, Marino; Ayora Piedrahita, Claudia Ximena (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Call centers must provide the level of service desired by the patient and required by health service entities and state regulatory entities. The objective is to improve the level of service by reducing the duration of calls by health call center agents by implementing the knowledge generation and transfer model for direction and management human processes. Lean Healthcare Six Sigma problem solving methodology is used. The creation, exchange, preservation and use of knowledge allowed continuous improvement.